(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides information on the development of science in Karakalpakstan, the number of scientific employees and scientific-pedagogical personnel, professors and teachers of the Pedagogical Institute, the establishment of the Karakalpak Scientific Research Institute, and the state of formation of scientific schools in social fields along with natural sciences.